تأثيرُ الجُرعَات المختلفةِ من السلفاكينوكزالين على بعضِ المعاييرِ الدَّمويَّةِ عندَ دجاجِ اللحم - حموية عبد الرزاق; المبارك حنان (Latakia University Journal -Biological Sciences Series, 2016)
استَهدَفت هذه الدراسةُ مَعرفةَ تأثير مُضاد للكوكسيديا(السلفاكينوكزالين)، المُنتشر في مزارعِ الدواجنِ في القطرِ العربيِّ السوريِّ، على بعضِ معاييرِ الكيمياحيويَّة، لدى فروجِ اللحمِ لأحدِ الهجنِ التِّجاريَّةِ نوع(Ross) المُتوفرة في سوريا. واستُخدمَ مُضادُ الكوكسيديا مَحلُ الاختبارِ بجُرعتين( الجُرعةِ العلاجيَّةِ وضعفِ العلاجيَّةِ)وهي (125)، (250)جزء بالمليون على التواليّ، حيثُ قُسِمَّت طيورُ التَّجربةِ البالغِ عَددها /120/ صوصاً بعمرِ يومِ واحد إلى ثلاثِ مجموعاتٍ مُتساويَّةِ هي: ]( الشاهد مج(1)، السلفاكينوكزالين مج(2) بتركيزِ(125) ppm، السلفاكينوكزالين مج(3) بتركيزِ ((250 [ppm، واستَمرت فترة التربية (45)يوماً، قُدِّمَ خلالها المُضاد بشكلٍ مُستمرٍ مع العلف، وجُمِعَت خلالَ هذه الفترةِ عيناتٌ دمويَّةٌ من المجموعاتِ الثلاثِ المُحددّةِ لفروجِ اللحمِ بعُمرِ(15- 30- 45) يوماً، ومن ثُمَّ أُجريَّت التحاليلُ المِخبريَّةُ للمعاييرِ الدَّمويَّةِ، والَّتي شمَلَت تركيزَ كُلٍّ البروتينِ(الكُلِّيّ) العامِ، الألبومينِ و الغلوبيولين في مصلِ الدَّم، وكذلكَ قيمَ تركيزِ كُلٍّ من العناصر المعدنيَّةِ(Ca،P، Mg) في مصل الدَّم. وقد انعكس تأثير السلفاكينوكزالين على المعايير الكيمياحيويَّةِ المدروسة عند دجاج اللحم وفقَ التاليّ: الانخفاض العامّ بمستوى البروتينِ الكُّلّيّ والألبومينِ خلالَ مرحلةِ السحبِ الثالثةِ في مجموعةِ السلفاكينوكزالين بالتركيزِ العلاجيِّ، وخلالَ جميعِ مراحلَ السحبِ بالتركيزِ ضعفِ العلاجيِّ. الفروقُ جاءَت معنويّةً بينَ المجموعتينِ المُختلفتينِ تركيزاً فيما يتعلقُ بتركيزِ البروتينِ الكلّيّ والألبومينِ في مصلِ الدَّمِ خلالَ المراحلَ الثلاثِ. الانخفاض العامّ فيما يتعلقُ بتركيزِ الغلوبيولين في مصلِ الدَّم خلالَ مرحلتيّ السحبِ الثانيّةِ والثالثةِ في مجموعة السلفاكينوكزالين بالتركيزِ العلاجيّ بمستوى معنويٍّ، وخلالَ مراحلَ السحبِ الثلاثِ في مجموعةِ السلفاكينوكزالين بالتركيزِ ضعفِ العلاجيّ بمستوى معنويًّ جداً. الانخفاض العامّ بمستوى كلٍّ من العناصرِ المعدنيَّةِ الثلاثِ(الكالسيوم- الفوسفور- المغنيزيوم) في مصلِ الدّمِ، خلالَ مرحلةِ السحبِ الثالثةِ في مجموعةِ السلفاكينوكزالين بالتركيزِ العلاجيّ، وخلالَ مراحلَ السحبِ الثلاثِ في مجموعةِ السلفاكينوكزالين بالتركيزِ ضعفِ العلاجيّ. الفروقُ جاءَت معنويّةً جداً فيما يتعلقُ بتركيزِ الكالسيوم، معنويّةً فيما يتعلقُ بتركيزِ كلٍّ من الفوسفور والمغنيزيوم عندَ المقارنةِ بين مجموعتيّ السلفاكينوكزالين المختلفتينِ تركيزاً. This study aimed to determine the effect of anticoccidial drug (Sulphaquinoxaline), that deployed in poultry farms in The Syrian Arab Republic, on some blood parameters, of broiler chickens for the commercial type(Ross), that available in Syria. We used drug being tested by two doses(therapeutic dose and a double therapeutic dose), as the following: (125, 250)ppm, respectively .The experience birds that braved /120/ chick at aged one day were divided to three equal distribution groups (Control, group(1), Sulphaquinoxaline, group(2) at concentration(125)ppm, Salafaquinoxaline, group(3) at concentration(250)ppm). The experience period continued for(45) days. The anticoccidial drug were presented continuously with fodder, and the blood samples were collected three times during this period. The blood samples were taken from broilers at the age(15 - 30 - 45) days. 10 samples were taken of each group from indentified three groups, then lab tests were done on the blood picture. These Tests included determination of the values of total protein, albumin and Globulin in blood serum, and also it included determination the values of some mineral elements in blood serum. These elements contained[Ca- P- Mg ] in serum. The effect of this anticoccidial drug reflected on studied biochemical parameters of broiler chickens in accordance as the following: Ageneral decline in the level of total protein and albumin in serum blood at the third stage of collection blood in group Sulphaquinoxaline at therapeutic concentration, and during the three stages of blood collection in group Sulphaquinoxaline at double therapeutic concentration. The differences between two groups were a significant at level (P<0.05). general decline in level of total globulin in serum blood at the second and the third stage of collection blood in group Sulphaquinoxaline at therapeutic concentration, at sighinificant level (P<0.05), and during the three stages of blood collection in group Sulphaquinoxaline at double therapeutic concentration at significant level (P<0.01). general decline in the level of mineral elements (Ca, P, Mg) in serum blood at the third stage of collection blood in group Sulphaquinoxaline at therapeutic concentration, and during the three stages of blood collection in group Sulphaquinoxaline at double therapeutic concentration. The differences between two groups were very significant at level (P<0.01) for calcium in serum and were a significant at level (P<0.05) for phosphorus and magnesium levels.